STUDENTS WHO LEARNED USING WHATSAPP GROUP MEDIA WITH STUDENTS WHICH LEARNING USING GOOGLE CLASSROOM MEDIA IN PANDEMIC TIME COVID-19 - Gilang Purnama (Journal Of Educational Experts (JEE), 2020)
So far, face-to-face learning has been the most effective learning model because it has been implemented in schools and has become the main choice to date. The Covid-19 pandemic that has hit various parts of the world in recent months has changed the habits of various aspects of life, including learning at school. The classic face-to-face learning method that has been a mainstay in schools suddenly has to change drastically with the online model. Whatsapp Group and Google Classroom are distance learning media that are familiar and often used. This study aims to compare the learning outcomes of students whose learners use WhatsApp group and those who use Google Classroom. This type of research is a quasi experiment. The research sample was 40 students of class VIII SMPN 1 Rawamerta and divided into two classes of 20 people each for classes using Whatsapp Group and 20 people using Google Classroom. The results showed that learning with Whatsapp Group was better than learning using Google Classroom. However, online learning still has several weaknesses, including poor signal and no internet quota.